If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(d + -7) = 6 Reorder the terms: 2(-7 + d) = 6 (-7 * 2 + d * 2) = 6 (-14 + 2d) = 6 Solving -14 + 2d = 6 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2d = 6 + 14 Combine like terms: -14 + 14 = 0 0 + 2d = 6 + 14 2d = 6 + 14 Combine like terms: 6 + 14 = 20 2d = 20 Divide each side by '2'. d = 10 Simplifying d = 10
| 4x-2(x-2)=-8+5x+6 | | 29-2x=209-7x | | 5(-3x-7)=3(9x-4) | | 3p-1-(p+3)=1 | | -2(-3y+5)-y=-9y+4 | | -(d-17)=2 | | -9x-9=72 | | .75-.357= | | 2.66=1.4(0.5z-z) | | 6(3y-2)=-(3y+5) | | -2(3x-5)=-4 | | v/3+(v-2)=2/3 | | x+x+3=108 | | y=x+9385 | | 7x-13=137-8x | | -11z-9-(-4)=-5z-z | | 2x-y+3z=7 | | -18-6x-4=17+1+2x | | 6.5x-4.8x+0.38=-2 | | 5-y=-8 | | 5x=12+4x | | x+15______=90 | | 7x+2x-5=10 | | 43x-10=42x-9 | | 3n-21=51 | | 0.875x-0.25+0.75x=0.166+x | | 25x+19=2x+180 | | pq+5p=13 | | 5-(8x-7)=31x-(90+28x)-45 | | 7x+4-4x-3=6 | | 8x+11=47-x | | -6z+9=8z-(-2) |